2016
DOI: 10.1177/1358863x16629728
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin levels are associated with arterial stiffness in healthy Korean adults

Abstract: Although an association between serum ferritin and atherosclerosis has been suggested, limited epidemiologic data are available regarding the association between ferritin and arterial stiffness in healthy adults. A total of 2932 healthy subjects were enrolled in this study. Anthropometric and biochemical profiles including ferritin were measured. The arterial stiffness was measured using brachial-ankle pulse wave velocity (baPWV). Serum ferritin levels were classified into quartiles and baPWV values gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…However, there is growing evidence demonstrating a strong association between higher serum ferritin levels and functional vascular damage. According with this, Ha et al reported, in a large cohort of healthy subjects, an association between ferritin and brachial-ankle PWV [20]. Moreover in haemodialysis patients, serum ferritin was associated with progressive arterial stiffness increase during a 3 years follow-up, but only for serum values > 500 ng/ml [21].…”
Section: Ferritin Glucose Metabolism and Atherosclerosis: A Complex mentioning
confidence: 89%
See 1 more Smart Citation
“…However, there is growing evidence demonstrating a strong association between higher serum ferritin levels and functional vascular damage. According with this, Ha et al reported, in a large cohort of healthy subjects, an association between ferritin and brachial-ankle PWV [20]. Moreover in haemodialysis patients, serum ferritin was associated with progressive arterial stiffness increase during a 3 years follow-up, but only for serum values > 500 ng/ml [21].…”
Section: Ferritin Glucose Metabolism and Atherosclerosis: A Complex mentioning
confidence: 89%
“…A recent meta-analysis shows 8 hat 1 m/s increase in PWV is associated with a 15% risk increase of CV mortality in about 16,000 individuals followed up for a mean of 8 years [17]. Although there is some evidence of an independent association between hyperferritinemia and arterial stiffness in disparate populations [18][19][20][21], data in hypertensive patients are few.…”
mentioning
confidence: 99%
“…However, there is growing evidence demonstrating a strong association between higher serum ferritin levels and functional vascular damage. According with this, Ha et al reported, in a large cohort of healthy subjects, an association between ferritin and brachial-ankle PWV [20]. Moreover in haemodialysis patients, serum ferritin was associated with progressive arterial stiffness increase during a three years follow-up, but only for serum values >500 ng/ml (21).…”
Section: Ferritin Glucose Metabolism and Atherosclerosis: A Complex mentioning
confidence: 89%
“…Scienti c evidence has shown that high glucose levels also in the prediabetic range and insulin resistance might lead to increased arterial stiffness and cardiac concentric remodeling [27], moreover in a sample of hypertensive patients a signi cant positive association between baseline brachial-ankle PWV and the risk of new-onset diabetes was found [28]. Also serum ferritin levels have been associated with new-onset T2DM risk in Chinese [29] and Korean [30] populations and with increased arterial stiffness in healthy Korean adults [20]. Moreover, besides classical confounders, 24hours ambulatory BP and hs-CRP levels were determinants of pharmacologically (empagli ozin) induced improvement of arterial stiffness parameters [31].…”
Section: Ferritin Glucose Metabolism and Atherosclerosis: A Complex mentioning
confidence: 99%
See 1 more Smart Citation